"Brownfields" - problém Euroregionu Nisa i EU jako celku - Kraft, Jiri ("Brownfields" - a problem of the Euro region Nisa as well of the EU as a whole, 2006)
Brownfields are a phenomenon rising as a result of an economy restructuring. That is involved by an entrance of countries into higher economic complexes, into integration alignments. Thus, an actual problem for all countries in the world and most for the new EU - members because the changes in GDP rates of particular sectors are in high-power progress. The problem brownfields is in connection with many economic effects, namely with multiplier effects. A cohesion with so called „opportunity costs”, as well negative and positive externalities, is obvious. An answer for the question „how to solve the phenomenon of brownfields” presents a specific chapter. A number of objects, which attended on the GDP output in primary and secondary sectors and which are not just now used, grow still. Can we rely on „the invisible hand of market”, or the government interventions are necessary? If the government interventions are strict, it will be necessary to optimize their scope. And the economic theory has its tools to it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 145-150